2021
DOI: 10.54536/ajaset.v5i2.78
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Yield and Resistance Effect of Some Yam Genotypes (Dioscorea rotundata Pior) to Pest Attack at Harvest in Uyo, Southeastern Nigeria

Abstract: Two years study was carried to assess level of resistance to yam beetle and termite attack by some yam genotypes in Uyo, southeastern Nigeria. The experiment was laid out in randomized complete block design replicated three times. The five yam genotypes tested for yam beetle and termite attack at harvest were; TDr 95/19127, 95/18894, 95/19531, 75/1/2 and Uyo popular local variety eteme. The results showed variations in yield and susceptible to termite and beetle attack at harvest. The TDr 75/1/2 had highest yi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 6 publications
1
8
0
Order By: Relevance
“…Also, the finding of Follett et al ( 2007) confirmed this fact that application of organic residues heighten soil organic carbon level. It also supports another assertion that addition of organic manures regularly is the only method to increase soil organic carbon status [18,19,20]. Olowoake [5] also found that addition of manure improves soil properties.…”
Section: Resultssupporting
confidence: 72%
“…Also, the finding of Follett et al ( 2007) confirmed this fact that application of organic residues heighten soil organic carbon level. It also supports another assertion that addition of organic manures regularly is the only method to increase soil organic carbon status [18,19,20]. Olowoake [5] also found that addition of manure improves soil properties.…”
Section: Resultssupporting
confidence: 72%
“…In sweet pepper, it has been reported that, poultry manure alone increased plant height, yield and yield component [24]. In the same line, [25] have shown that the application of organic fertilizer affects the Journal of Agricultural Chemistry and Environment growth of soybeans. The increase in growth with poultry manure might be due to increase in nutrients supply that improved on the crop growth and the high level of organic matter also enhances the physico-chemical properties of the soil.…”
Section: Discussionmentioning
confidence: 88%
“…The actual number of roots which eventually from tubers depends on several factors including genotypes, assimilate supply, photoperiod and temperature (IITA, 1990; Ikeh eta al, 2012). Despite genetic makeup of the crop, resistance to biotic stress such as insect pest, pathogens, nematodes also would encourage good quality tubers (Ikeh, 2010 andIkeh et al, 2012). Tuber yield also is a dependent on its photosynthetic efficiency and assimilation rate of such yam cultivar which usually correlate with leaf area, leaf area duration and crop management practices.…”
Section: Discussionmentioning
confidence: 99%